Investigation On The Mechanical Properties Of Hybrid Fibre Metal Laminate - Jumaat, Faizal Azli (2016)
The main purpose of this research is to investigate the mechanical properties of hybrid fibre-metal-laminate (FML) with different orientations composites. The mechanical responses of FML composites reinforced by three layers of natural fibre or in combination with glass fibres were compared against those of different ply orientation and laminate layup. The tensile moduli of elasticity of the FML composites with various laminate layup were comparable to those of FML composites with different ply orientation. The ultimate tensile strengths and strain at failure of the FML composite with different ply orientation and laminate layup were also investigate. The mechanical response trends under impact of FML composites were compared against those of flatwise and edgewise of impact test. The FML laminates based on aluminium alloy 5052-0 connected with polypropylene adhesive film, polypropylene (PP), glass fibre (G) and kenaf fibre (K). The low velocity impact tests were performed by using impact pendulum tester according to ASTM E-23 standard and the tensile behaviour generally investigated using universal testing machine according to ASTM D 3039 standard. The effects of ply orientation (0°-90° I 45°-45°) and laminate layup (GGGIKKK/GKG/KGK) on the mechanical responses of the FMLs were also investigated. The morphological properties of FML composite samples were analysed through stereo microscope images and these clearly demonstrated the better interfacial adhesion between the woven kenaf fibre, woven glass fibre and the polypropylene matrix with different orientation. Result shows that, 50% reductions by weight for FML compared to monolithic aluminium, FML incorporating 45°/-45 woven orientations had inferior tensile properties in comparison to FML composites reinforced by 0°/90° woven orientation and FML layup with GKG shows the superior at both test methods.